simplifique:
(2x-3y) (2x+3y) - (3x-2y)²
Soluções para a tarefa
Respondido por
5
4x² - 9y² - ( 9x² - 12xy + 4y² ) =
4x² - 9y² - 9x² + 12xy - 4y² =
-5x² - 13y² + 12xy =
5x² + 13y² - 12xy
4x² - 9y² - 9x² + 12xy - 4y² =
-5x² - 13y² + 12xy =
5x² + 13y² - 12xy
Respondido por
4
= (2x - 3y) . (2x + 3y) - (3x - 2y)²
= 2x.2x + 2x.3y - 3y.2x - 3y.3y - [ (3x)² - 2.3x.2y + (2y)²]
= 4x² + 6xy - 6xy - 9y² - [ 9x² - 12xy + 4y²]
= 4x² - 9y² - 9x² + 12xy - 4y²
= 4x² - 9x² - 9y² - 4y² + 12xy
= - 5x² - 13y² + 12xy
= - 5x² + 12xy - 13y²
= 2x.2x + 2x.3y - 3y.2x - 3y.3y - [ (3x)² - 2.3x.2y + (2y)²]
= 4x² + 6xy - 6xy - 9y² - [ 9x² - 12xy + 4y²]
= 4x² - 9y² - 9x² + 12xy - 4y²
= 4x² - 9x² - 9y² - 4y² + 12xy
= - 5x² - 13y² + 12xy
= - 5x² + 12xy - 13y²
Perguntas interessantes
Matemática,
1 ano atrás
Química,
1 ano atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás